Adenoid hypertrophy and nocturnal enuresis are associated with sleep disturbances - Uzun Cicek, Ayla; Bora, Adem; Elif Altuntas, Emine (ENT Updates, 2020)
Objective: Adenoid hypertrophy and nocturnal enuresis, comorbidities that are quite prevalent among children, are both associated with sleep problems. However, limited research has specifically focused on sleep domains and their parameters. In the present study we thus aimed to investigate the impact of adenoid hypertrophy and nocturnal enuresis on sleep, both when the two disorders coexist and when they do not coexist. Methods: We investigated 178 children (mean age: 7.24±1.02 years, range=6-9 years), 50 (28.1%) of whom had only adenoid hypertrophy, 39 (21.9%) of whom had only nocturnal enuresis, 35 (19.7%) of whom had coexistence of adenoid hypertrophy and nocturnal enuresis, and 54 (30.3%) of whom were healthy-control children. Psychiatric disorders were diagnosed by a semi-structured diagnosis interview and the diagnosis of adenoid hypertrophy was confirmed by flexible fiberoptic nasopharyngoscopy. Sleep habits and disturbances were assessed via the Children’s Sleep Habits Questionnaire and Modified Epworth Sleepiness Scale. Results: Our results showed that the comorbid condition was the most severe form in terms of both adenoid hypertrophy and enuresis. Regarding sleep difficulties, the “Sleep-Disordered Breathing”, “Night Wakings”, “Sleep Onset Delay” and “Sleep Duration” parameters were closely associated with adenoid hypertrophy and its severity, while “Bedtime Resistance”, “Parasomnias” and “Sleep Anxiety” domains of sleep were strongly related to nocturnal enuresis. Conclusion: Otorhinolaryngologists, child psychiatrists and pediatricians should be aware of the relationship between enuresis and adenoid hypertrophy, that both diseases are associated with impaired sleep patterns, and that children affected by the comorbidity of the two disorders experience more sleep disturbances.